Development of Learning Concepts For Natural Resources Materials Teaching In High School Students - Evi Apriana (Jurnal Serambi Ilmu, 2024)
This study aims to determine how the development of learning the concept of conserving biological natural resources (SDAH) in high school students through a community science technology approach (STS) with a roleplaying method. This research is qualitative in nature, an analysis of the development of learning the concept of conservation of natural resources is carried out through the STS approach with a role-playing method related to Aceh’s environmental issues. A trial was conducted on a limited scale on the implementation of learning in class X-4 with 34 students as a subject in one of the State Senior High Schools in Darul Imarah District, Aceh Besar District. Data were collected by classroom observation, interviews and concept understanding tests. The results showed that the development of learning the concept of conservation of SDAH can be done through the STS approach with the role playing method, can increase students’ motivation, creativity in learning; By playing a role, students can place themselves as if they were in a real situation so that they can instill roles, understand concepts, can improve science and technology for the preservation of living natural resources related to Aceh’s environmental issues.